Examining Surgical Patients’ Expectations of Nursing Care at Kenyatta National Hospital in Nairobi, Kenya - Shawa, Elwin; Omondi, Lilian; Mbakaya, Balwani Chingatichifwe (European Scientific Journal, ESJ, 2017)
Good service is defined when it meets the expectations of its customers. Likewise, nursing is a profession that aims at meeting patients’ needs and expectations. Many studies have been done at Kenyatta National Hospital (KNH) in Nairobi, Kenya regarding customer care satisfaction in various departments. However, little is known on patients’ expectations regarding nursing care. Therefore, this study was carried out to examine surgical patients’ expectations of nursing care in surgical wards. A descriptive cross-sectional quantitative study was conducted at Kenyatta National Hospital in general surgical wards from April to June, 2012. The study population were adult postoperative patients admitted in the general surgical wards. The sample size was 168 and systemic random sampling technique was used in selecting the participants. The data collection tool was a structured questionnaire with open and closed questions. Ethical clearance was obtained from University of Nairobi and Kenyatta National Hospital Ethics Committee. Participation in the study was voluntary and based on patients’ ability to give informed consent. A total of 167 adult patients from general surgical wards responded to the questionnaire. Most patients agreed that they expected nurses to be knowledgeable with an average response of 86% and strongly disagreed that nurses should be rude and harsh (44%). 46% of participants agreed that they expected nurses to be responsive with mean of (M=3.61). It was found that most patients’ expectations were met and because of this, many felt satisfied with the nursing care provided. It is recommended that nurses should pay more attention to what patients expect from nursing care.